Does Sales Growth Moderate in Financial Difficulties? (International Forum of Researchers and Lecturers, 2025)
This study emphasizes the significance of profitability and liquidity as key indicators of financial performance, particularly within the property and real estate sector. This industry is highly sensitive to economic fluctuations and urban development changes, which can directly impact a company's ability to manage its financial resources effectively. The research investigates the interaction between these financial variables in determining financial stability across companies operating in this sector. Specifically, the study aims to examine and analyze the effects of profitability and liquidity on financial distress, with sales growth as a moderating variable, using data from property and real estate companies listed on the Indonesia Stock Exchange during the 2021–2023 period. The research relies on secondary data and applies purposive sampling to select a total of 26 companies that meet the specified criteria. The analytical approach involves hypothesis testing and Moderated Regression Analysis (MRA), utilizing SPSS version 25 as the statistical tool. The findings reveal that profitability has a significant negative effect on financial distress, suggesting that higher profitability reduces the likelihood of financial difficulties. Conversely, liquidity is found to have a significant positive effect on financial distress, indicating that higher liquidity may be associated with greater financial challenges in this sector—potentially due to inefficient cash management or excessive short-term liabilities. However, the study finds that sales growth does not significantly moderate the relationship between profitability and liquidity in influencing financial distress. These results offer important insights for stakeholders in the property and real estate industry, highlighting the need for balanced financial strategies that enhance profitability while maintaining healthy liquidity levels. The findings also suggest that simply increasing sales growth may not be sufficient to offset financial difficulties if core financial indicators are not properly managed.